Effectiveness of Endobronchial Ultrasound-Guided Transbronchial Biopsy Combined With Tissue Culture for the Diagnosis of Sputum Smear-Negative Pulmonary Tuberculosis - Lin, Ching-Kai; Fan, Hung-Jen; Yu, Kai-Lun; Chang, Lih-Yu; Wen, Yueh-Feng; Keng, Li-Ta; Ho, Chao-Chi (Frontiers in Microbiology, 2022)
Background: Microorganisms of tuberculosis (TB) are frequently difficult to identify from the airway specimen, therefore lung biopsy for further histologic and microbiologic study is required. Endobronchial ultrasound-guided transbronchial biopsy (EBUS-TBB) is used for the diagnosis of pulmonary malignancy, but is rarely in the TB population. The purpose of this study was to verify the effectiveness and safety of EBUS-TBB with histologic study and tissue culture in the diagnosis of sputum smear-negative pulmonary TB. Methods: Patients who underwent EBUS-TBB with histologic study and TB tissue culture for clinically suspected, but sputum smear-negative pulmonary TB from January 2016 to December 2018 were included. The accuracy of each diagnostic modality was calculated respectively. Factors that might influence the positive rate of TB culture (washing fluid and tissue specimen) were also evaluated. Results: One hundred sixty-one patients who underwent EBUS-TBB for clinically suspected, but sputum smear-negative pulmonary TB were enrolled, and 43 of them were finally diagnosed as having pulmonary TB. The sensitivity of washing fluid and tissue specimen via EBUS-TBB for TB diagnosis were 48.8 and 55.8%, respectively. The sensitivity for TB diagnosis would be elevated to 67.4% when both washing fluid and tissue specimens are used. The positive TB culture rate would not statistically increase with a combination of tissue specimens and washing fluid. Univariate analysis revealed that TB microorganisms would be more easily cultivated when lesions had an abscess or cavity on the computed tomography image (presence vs. absence; 62.5% vs. 26.3%, P = 0.022), heterogeneous echogenicity on the EBUS finding (heterogeneous vs. homogeneous; 93.3% vs. 21.4%, P = 0.001), or a necrotic pattern via histologic study (presence vs. absence; 70.6% vs. 30.8%, P = 0.013). Heterogeneous echogenicity was the independent predictor according to the results of multivariate analysis. None of our patients encountered major adverse events or received further intensive care after EBUS-TBB. Conclusion: EBUS-TBB is safe and effective for use in diagnosing sputum smear-negative pulmonary TB. EBUS echoic feature is also a predictor of the positive TB culture rate in pulmonary TB. However, tissue culture via EBUS-TBB has little effect in improving the positive TB culture rate.